Lightning effects on underground distribution cable using alternative transient program - Abd Rahim, Mohamad Hafiz (2015)
Underground cable is commonly used in situation where power need to be transmitted across river or sea or through heavily populated areas. Even though underground cables are not directly exposed to hazard, lightning can induce a potential on the insulation of the underground cable. About 80% of the lightning strikes in Malaysia produce voltage in excess of 20 kV. This study was done to determine the possibility of having insulation breakdown of the underground cable either by direct stroke or by induction. The simulation was performed using Alternative Transient Program version of the Electromagnetic Transients Program (ATP-EMTP) software to determine whether the induced voltage due to lightning can cause any insulation breakdown. A network system consisting of 33kV Cu/XLPE/CWS/PVC/HDPE insulated armoured Polyvinyl Chloride (PVC) sheathed cable rated was modelled. A 40 kV lightning current with 1.2/50 μs characteristic has been injected into the system. Several models cable and also soil to represent the whole system in electronic circuit have been designed and analyzed. This study shows the difference in various parameter across the shield and the sheath of the cable distribution of the best among the different types of armor and sheath used.